Effectiveness Of Lower Limb Strengthening Program on Functional Mobility in Multiparrous Women - Gaikwad, Diksha Vikrant; Kanase, Suraj B. (Journal of Neonatal Surgery, 2025)
Background Pregnancy is a transformative and special time in woman’s life marked by physiological, anatomical emotional and hormonal changes in the women’s body affecting various system of the body such as cardiovascular, respiratory, endocrine, renal and musculoskeletal systems. These changes are essential to meet the mother’s increased metabolic demand support the foetal development and help both the mother and foetus prepare for childbirth. Methods This study was an experimental study which includes 60 multiparrous women in and around Karad residing in urban and rural areas were taken and consent form was signed by the participants were explained regarding the test and it was undertaken. Result As there were 2 groups that is group A and group B and the data was prepared for each group as it was divided by 1-2 wks , 2-4 wks . 4-6 wks and each muscle group.For the experimental group , the p-value for muscle strength was 0.02 indicating a statistically significant change in muscle strength over the time . . For the control group , the p-value for muscle strength was 0.08 indicating no significant change in muscle strength. The study findings indicates that 35% of women experiencedsignificant improvement in functional mobility following the lower limb strengthening program in multiparous women. In contrast 25% showed no notable improvements. Conclusion The study suggest that a lower limb strengthening program cam enhance functional mobility in multiparous women program significantly improves functional mobility in multiparous women. This data suggests that the intervention used in the Experimental Group has a substantial impact on improving muscle strength compared to the Control Group.